Question Number 171244 by mathlove last updated on 11/Jun/22 | ||
![]() | ||
$$\frac{{x}}{{y}}+\frac{{y}}{{x}}=\frac{\mathrm{26}}{\mathrm{5}} \\ $$$$\frac{{x}+{y}}{{x}−{y}}=? \\ $$$$\frac{}{} \\ $$ | ||
Commented by infinityaction last updated on 11/Jun/22 | ||
![]() | ||
$$\frac{{x}^{\mathrm{2}} +{y}^{\mathrm{2}} }{\mathrm{2}{xy}}\:=\:\frac{\mathrm{26}}{\mathrm{10}} \\ $$$$\frac{{x}^{\mathrm{2}} \:+\:{y}^{\mathrm{2}} \:+\mathrm{2}{xy}}{{x}^{\mathrm{2}} +{y}^{\mathrm{2}} −\mathrm{2}{xy}}\:\:=\:\frac{\mathrm{36}}{\mathrm{16}} \\ $$$$\left(\frac{{x}+{y}}{{x}−{y}}\right)^{\mathrm{2}} \:=\:\frac{\mathrm{36}}{\mathrm{16}} \\ $$$$\frac{{x}+{y}}{{x}−{y}}\:=\:\pm\frac{\mathrm{3}}{\mathrm{2}} \\ $$ | ||
Commented by Rasheed.Sindhi last updated on 11/Jun/22 | ||
![]() | ||
$$\mathcal{GOOD}! \\ $$ | ||
Commented by udaythool last updated on 11/Jun/22 | ||
![]() | ||
$${super} \\ $$ | ||
Answered by Rasheed.Sindhi last updated on 11/Jun/22 | ||
![]() | ||
$$\begin{array}{|c|}{\frac{{x}}{{y}}+\frac{{y}}{{x}}=\frac{\mathrm{26}}{\mathrm{5}}\:\:;\:\:\frac{{x}+{y}}{{x}−{y}}=?}\\\hline\end{array} \\ $$$${a}+\frac{\mathrm{1}}{{a}}=\frac{\mathrm{26}}{\mathrm{5}} \\ $$$$\mathrm{5}{a}^{\mathrm{2}} −\mathrm{26}{a}+\mathrm{5}=\mathrm{0} \\ $$$$\left({a}−\mathrm{5}\right)\left(\mathrm{5}{a}−\mathrm{1}\right)=\mathrm{0} \\ $$$${a}=\mathrm{5}\:\mid\:\:{a}=\frac{\mathrm{1}}{\mathrm{5}} \\ $$$$\frac{{x}}{{y}}=\mathrm{5}\:\:\mid\:\frac{{x}}{{y}}=\frac{\mathrm{1}}{\mathrm{5}} \\ $$$$\bullet\:\frac{{x}+{y}}{{x}−{y}}=\frac{\cancel{{y}}\left(\frac{{x}}{{y}}+\mathrm{1}\right)}{\cancel{{y}}\left(\frac{{x}}{{y}}−\mathrm{1}\right)}=\frac{\frac{{x}}{{y}}+\mathrm{1}}{\frac{{x}}{{y}}−\mathrm{1}} \\ $$$$=\frac{\mathrm{5}+\mathrm{1}}{\mathrm{5}−\mathrm{1}}\:\:\mid\:=\frac{\mathrm{1}/\mathrm{5}+\mathrm{1}}{\mathrm{1}/\mathrm{5}−\mathrm{1}}=\frac{\mathrm{1}+\mathrm{5}}{\mathrm{1}−\mathrm{5}}=\frac{\mathrm{6}}{−\mathrm{4}} \\ $$$$=\frac{\mathrm{3}}{\mathrm{2}}\:\mid\:=−\frac{\mathrm{3}}{\mathrm{2}} \\ $$ | ||
Answered by Rasheed.Sindhi last updated on 11/Jun/22 | ||
![]() | ||
$$\underset{\left({i}\right)} {\underbrace{\frac{{x}}{{y}}+\frac{{y}}{{x}}=\frac{\mathrm{26}}{\mathrm{5}}}}\:;\:\frac{{x}+{y}}{{x}−{y}}=?\: \\ $$$$\frac{{x}+{y}}{{x}−{y}}=\frac{{p}}{{q}}\:\left({say}\right) \\ $$$$\frac{{x}}{{y}}=\frac{{p}+{q}}{{p}−{q}} \\ $$$$\left({i}\right)\::\:\:\:\frac{{p}+{q}}{{p}−{q}}+\frac{{p}−{q}}{{p}+{q}}=\frac{\mathrm{26}}{\mathrm{5}} \\ $$$$\frac{\left({p}+{q}\right)^{\mathrm{2}} +\left({p}−{q}\right)^{\mathrm{2}} }{\left({p}−{q}\right)\left({p}+{q}\right)}=\frac{\mathrm{26}}{\mathrm{5}} \\ $$$$\frac{\mathrm{2}\left({p}^{\mathrm{2}} +{q}^{\mathrm{2}} \right)}{{p}^{\mathrm{2}} −{q}^{\mathrm{2}} }=\frac{\mathrm{26}}{\mathrm{5}} \\ $$$$\frac{{p}^{\mathrm{2}} +{q}^{\mathrm{2}} }{{p}^{\mathrm{2}} −{q}^{\mathrm{2}} }=\frac{\mathrm{26}}{\mathrm{10}} \\ $$$$\frac{{p}^{\mathrm{2}} }{{q}^{\mathrm{2}} }=\frac{\mathrm{36}}{\mathrm{16}}=\frac{\mathrm{9}}{\mathrm{4}} \\ $$$$\frac{{p}}{{q}}=\pm\frac{\mathrm{3}}{\mathrm{2}} \\ $$$$\frac{{x}+{y}}{{x}−{y}}=\pm\frac{\mathrm{3}}{\mathrm{2}} \\ $$$$\mathcal{F}{ormula}\:\mathcal{U}{sed}: \\ $$$$\begin{array}{|c|}{\underset{} {\overset{\bullet} {\:\begin{array}{|c|}{\frac{{a}}{{b}}=\frac{{c}}{{d}}\Rightarrow\frac{{a}+{b}}{{a}−{b}}=\frac{{c}+{d}}{{c}−{d}}}\\\hline\end{array}_{} ^{} }}}\\\hline\end{array} \\ $$ | ||
Commented by mathlove last updated on 11/Jun/22 | ||
![]() | ||
$${thanks} \\ $$ | ||
Commented by haladu last updated on 11/Jun/22 | ||
awesome solution | ||
Commented by Rasheed.Sindhi last updated on 11/Jun/22 | ||